Efficient biorefinery of waste activated sludge and vinegar residue into volatile fatty acids: effect of feedstock conditioning on performance and microbiology. Issue 11 (21st June 2018) - Zhou, Aijuan; Liu, Zhihong; Varrone, Cristiano; Luan, Yunbo; Liu, Wenzong; Wang, Aijie; Yue, Xiuping
Abstract : Biorefinery of waste activated sludge into carboxylic acids, particularly low molecular fatty acids, is of major interest due to its carbonaceous characteristics. Abstract : Carboxylic acids, particularly short chain (C2 and C3) fatty acids, are the preferable carbon source for many bioprocesses. Production efficiency of volatile fatty acids (VFAs) recovery from waste activated sludge (WAS) is limited by unbalanced nutrient components. In this study, a low-cost alternative approach ( i.e., co-digestion with vinegar residue (VR)) to enhance C2–C3 VFAs recovery from WAS is reported. Compared to sole WAS digestion, concentration of total VFAs, C2–C5, increased by 187%, 74% and 44%, when co-digested with thermal-assisted alkaline (TA), ammonium hydroxide (AH) and sulfuric acid (SA) pretreated VR, respectively. Based on composition analysis, this improvement was mainly due to C2–C3 VFAs production. The hydrolysis rate constants in co-digestion tests, e.g., k h_TA = 0.0045 h −1, were also higher than that observed during mono-digestion (0.0018 h −1 ). Addition of VR greatly increased the hydrolysis of WAS, particularly with TA, thus enhancing the subsequent acidification process. High-throughput sequencing illustrated that certain groups of microbes (particularly hydrolytic and acid-producing bacteria), such as Acetobacterium, Proteiniclasticum, Cloacibacillus, Acinetobacter and Gemmobacter, were enriched in WAS and VR co-digestion. Further investigation of canonical correlation analyses showed that characteristic conditioning of digestion feedstock was an efficient strategy to restructure the inherent microbial community in WAS. The proposed concept in this study may be practical to simultaneously reduce operational, sludge transport and disposal costs of WWTPs.